Myanmar Monthly Food Price Report – November 2025 - Htar, May Thet; Minten, Bart; Masias, Ian (International Food Policy Research Institute, 2025)
Rice prices in November 2025 declined nationally, falling by 13 percent year-on-year and remaining broadly stable compared to the previous month. The decline continues to be driven by international market trends and downward pressure from the incoming monsoon harvest.